Bridging Law and Practice in Natural Resource Governance: A Narrative Review - Hermansyah (Indonesian Scientific Publication, 2024)
Legal frameworks for natural resource governance play a critical role in determining equitable access, sustainable use, and environmental protection. This study aims to synthesize current research on legal structures governing natural resources, with a particular focus on marginalized communities in developing countries. A narrative review approach was employed, utilizing scholarly databases such as Scopus and Google Scholar. Boolean keyword combinations including